2016
DOI: 10.2147/ijnrd.s121492
|View full text |Cite
|
Sign up to set email alerts
|

Does calcium channel blockade have a role in prevention of expression of sepsis in renal transplant recipients?

Abstract: Abstract:Many antihypertensive agents have been demonstrated to assist in preservation of kidney function, among them those that modulate calcium channels. Calcium channel blockers may also be of value in protecting hemodialysis patients from complications of sepsis. In diabetic recipients of kidney transplant allografts treated with cyclosporine, calcium channel blockade has been retrospectively linked to improved graft preservation and to fewer episodes of sepsis. This brief review outlines clinical and expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Although there has been considerable interest in blocking of calcium channels for the control of various multidrug resistant infectious diseases including malaria, schistosomiasis, tuberculosis, and inflammatory responses, [5][6][7][8][9][10][11][12][13][14][15][16][17] our retrospective analysis of this large renal transplant trial database does not provide any support for the hypothesis that calcium channel blocking agent use provides protection from infectious, all-cause, or cardiovascular mortality. A recent study also demonstrated that calcium sensitizing agents would not improve organ dysfunction in sepsis.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Although there has been considerable interest in blocking of calcium channels for the control of various multidrug resistant infectious diseases including malaria, schistosomiasis, tuberculosis, and inflammatory responses, [5][6][7][8][9][10][11][12][13][14][15][16][17] our retrospective analysis of this large renal transplant trial database does not provide any support for the hypothesis that calcium channel blocking agent use provides protection from infectious, all-cause, or cardiovascular mortality. A recent study also demonstrated that calcium sensitizing agents would not improve organ dysfunction in sepsis.…”
Section: Discussionmentioning
confidence: 74%
“…In vitro and prior observational studies have suggested that the use of calcium channel blocking agents may decrease the expression of sepsis in resistant infections or enhance antibiotic effectiveness in differing nontransplant populations. [5][6][7][8][9][10][11][12][13][14][15][16][17] Our retrospective study suggested a beneficial impact of calcium channel blocking agents on prevalence of sepsis in immunosuppressed transplant recipients, 1 a population that has not been prospectively studied. We, therefore, performed a post hoc analysis of a large 2 Weinrauch et al prospective trial of renal transplant recipients 18 to determine the difference in prevalence of cardiovascular, noncardiovascular (including infection related), and all-cause deaths between the two groups of patients, ie, those receiving CCB and those not.…”
Section: Introductionmentioning
confidence: 84%